2017
DOI: 10.1080/15548627.2017.1320633
|View full text |Cite
|
Sign up to set email alerts
|

Plant Bax Inhibitor-1 interacts with ATG6 to regulate autophagy and programmed cell death

Abstract: Autophagy is an evolutionarily conserved catabolic process and is involved in the regulation of programmed cell death during the plant immune response. However, mechanisms regulating autophagy and cell death are incompletely understood. Here, we demonstrate that plant Bax inhibitor-1 (BI-1), a highly conserved cell death regulator, interacts with ATG6, a core autophagy-related protein. Silencing of BI-1 reduced the autophagic activity induced by both N gene-mediated resistance to Tobacco mosaic virus (TMV) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 87 publications
2
78
0
Order By: Relevance
“…For example, a lack of conservation between plant and animal BI1 protein has been established in relation to the ER calcium-leak role observed for BI1 in animals, but not in plants (Bultynck et al, 2012), and for the modulation of the accumulation of ER-generated reactive oxygen species (ROS) by BI1 established in animals (Kim et al, 2009), but not in plants (Kawai-Yamada et al, 2004). Furthermore, in animals BI1 negatively regulates autophagy under nutrient starvation (Castillo et al, 2011), whereas in plants it activates autophagy, inducing cell death (Xu et al, 2017). In agreement with these findings, in our work we have demonstrated that the loss of BI1 does not affect plant ER stress resistance, supporting the hypothesis that the anti-apoptotic role of BI1 is not conserved.…”
Section: Ire1-independent Role Of Bzip60 In Er Stress Recoverymentioning
confidence: 99%
“…For example, a lack of conservation between plant and animal BI1 protein has been established in relation to the ER calcium-leak role observed for BI1 in animals, but not in plants (Bultynck et al, 2012), and for the modulation of the accumulation of ER-generated reactive oxygen species (ROS) by BI1 established in animals (Kim et al, 2009), but not in plants (Kawai-Yamada et al, 2004). Furthermore, in animals BI1 negatively regulates autophagy under nutrient starvation (Castillo et al, 2011), whereas in plants it activates autophagy, inducing cell death (Xu et al, 2017). In agreement with these findings, in our work we have demonstrated that the loss of BI1 does not affect plant ER stress resistance, supporting the hypothesis that the anti-apoptotic role of BI1 is not conserved.…”
Section: Ire1-independent Role Of Bzip60 In Er Stress Recoverymentioning
confidence: 99%
“…Moreover, autophagic cell death, which is regarded as one of the major PCD types, has been well studied in animals, including in C. elegans and D. melanogaster (Martin et al , ; Samara et al , ; Mariño et al , ). In plants, PCD and autophagy are usually found simultaneously in various cellular responses, like pathogen‐induced hypersensitive response (Xu et al , ), leaf senescence (Ono et al , ), xylem fiber development (Courtois‐Moreau et al , ) and microspore embryogenesis (Bárány et al , ). Additionally, emerging evidence suggests that autophagy is involved in the regulation of PCD during plant sexual reproduction (Minina et al , ; Xu et al , ).…”
Section: The Roles Of Autophagy In Key Processes Of Plant Reproductionmentioning
confidence: 99%
“…In plants, PCD and autophagy are usually found simultaneously in various cellular responses, like pathogen‐induced hypersensitive response (Xu et al , ), leaf senescence (Ono et al , ), xylem fiber development (Courtois‐Moreau et al , ) and microspore embryogenesis (Bárány et al , ). Additionally, emerging evidence suggests that autophagy is involved in the regulation of PCD during plant sexual reproduction (Minina et al , ; Xu et al , ). Therefore, the crosstalk between PCD and autophagy is often speculated and discussed.…”
Section: The Roles Of Autophagy In Key Processes Of Plant Reproductionmentioning
confidence: 99%
“…Silencing of tobacco BI-1 reduced the autophagy activity induced by virus infection or oxidative stress, while overexpression of BI-1 increased autophagy activity and caused autophagydependent cell death (Xu et al, 2017). BI-1 therefore has both autophagy-dependent prosurvival and prodeath effects, depending on the conditions.…”
Section: Other Possible Regulatorsmentioning
confidence: 99%
“…Third, the plant Bax inhibitor-1 (BI-1) has recently been shown to interact with ATG6 in vivo and in vitro and to positively regulate autophagy (Xu et al, 2017). Silencing of tobacco BI-1 reduced the autophagy activity induced by virus infection or oxidative stress, while overexpression of BI-1 increased autophagy activity and caused autophagydependent cell death (Xu et al, 2017).…”
Section: Other Possible Regulatorsmentioning
confidence: 99%